Study on emergency response preparedness of hazardous materials transportation - Aini, M.S.; Fakhru'l-Razi, A.; Ibrahim, W.M.N.; Tangavelu, S.K.; Daud, M. (Emerald, 2001)
Notes the recent increase in interstate shipments ofhazardous materials, by road, in Malaysia following rapid expansion in the manufacturing sector. Although there has been no major accident involving transportation of hazardous materials, the high rate of road accidents has raised great concerns concerning motor vehicles carrying hazardous goods and petroleum products. Determines the emergency preparedness and response plans of the transportation companies. Data were obtained from management and drivers, and the results revealed that the companies did not have a proper management system of safe transportation, had inadequate training of personnel, and the transport vehicles were not provided with appropriate tools and equipment for emergency response during mishaps. The drivers lacked general awareness and principal knowledge of hazardous material emergency response. Suggests that there is an urgent need to stipulate legal requirements for hazardous material transportation in Malaysia.